A boxers motor actions rationalization on the basis of regularities of higher nervous activity - Kolesnik, I. S.; Gatin, F. A. (The Russian Journal of Physical Education and Sport, 2018)
The problem of technical-tactical mastery improvement among boxers, the search for new reserves, which provide sportsmanship increase, attract attention of many specialists, as these problems solution conditions the effectiveness of competitive activity. The period of initial sports training in boxing lasts two-three years; its duration can be reduced owing to a rational training process organization. Material. The article is about the physiological mechanism of motor actions rationalization on the basis of taking into consideration the regularities of higher nervous activity functioning. During a boxing combat sportsman experience different external stimulus, which condition corresponding reaction. This reaction can be both positive and negative. The ability to concentrate nervous-muscular efforts on the main stimulus helps to control effectively competitive activity. Research methods: scientific-methodical literature analysis, pedagogical experiment, testing. Results. For a successful technique fulfillment it is important to take into consideration the necessity to alternate muscular tension and relaxation, which will help to fulfill an effective attack in proper time in accordance with own program of actions. The methodology of a rational techniques organization skills formation includes the system of motor tasks, directed toward combatant`s readiness provision for a boxing combat conduct in different, unusual, difficult conditions of competitive activity. The unexpected situations, which prevent the set aims realization, can be the following: a tall opponent, considerable length of the upper extremity; unusual time of competitions organization, conditioned by time zones change and etc. Training for a rational motor activity organization was realized by means of the methodical techniques use system, directed toward stability of psychic and physical abilities provision during conditions creation, which provide latent qualities of an organism revelation, as an important factor of the planned result achievement. Conclusion. The initial stage of sports training among boxers can be considerably reduced owing to a rational motor activity organization on the basis of higher nervous activity regularities use. The created methodology of the rational motor activity organization skills formation helped to improve the indices of physical and technical readiness among boxers of mass categories.